Development of Communicative Arabic Books Based on Local Wisdom through a Deep Learning Approach to Improve Students' 6Cs Skills/Pengembangan Buku BahasaArab Komunikatif Berbasis Kearifan Lokal melalui Pendekatan Deep Learning untuk Meningkatkan Keterampilan 6Cs Mahasiswa - Hajar Nurma Wachidah; Ulil Nurul Imanah; Puty Nurma Chairani; Fatma Maulla Aliffi; Istiqlalia Kamaliah Al-khoir (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2025)
The demands of the 21st century, commonly known as the 6Cs, namely communication, character, collaboration, critical thinking, citizenship, and creativity, encourage educators to implement learner-centered learning that accommodates the 6Cs skills through the use of technology. The background of this study is that the 6Cs skills in language learning have not been fully achieved in Indonesia, especially in Arabic, because the learning process has not been equipped with steps that support these 6Cs skills, and educators tend to only deliver material rather than ask questions that trigger active participation from students. In addition, the improvement of 6Cs skills has not been fully considered in the learning process by educators at Islamic Univertsity of Majapahit, Mojokerto. This study uses the Borg and Gall R&D research design. The results of this study indicate that the application of a learning model that accommodates the 6Cs skills, namely problem-based learning with technology integration, has a significant impact on increasing the effectiveness of the 6Cs skills (collaboration, character, creativity, critical thinking, citizenship, and communication) in Arabic language subjects. Through local wisdom-based digital project-based learning with a deep learning approach, students are able to interact actively and enjoy learning more.Tantangan integrasi keterampilan global Abad ke-21 yakni keterampilan 6Cs dengan pembelajaran Bahasa Arab yang sering terfragmentasi. Diperlukan inovasi media digital yang memicu pemahaman mendalam (deep learning) dan kontekstual. Penelitian ini bertujuan mengetahui efektivitas pengembangan Arabic Book Creator Digital yang mengintegrasikan nilai-nilai kearifan lokal sebagai materi autentik untuk meningkatkan kompetensi 6Cs. Penelitian ini menggunakan desain penelitian R&D model Borg dan Gall. Hasil penelitian ini menunjukkan bahwa penerapan model pembelajaran yang mengakomodasi 6Cs, yaitu project-based learning dengan integrasi teknologi, memiliki dampak signifikan terhadap peningkatan efektivitas keterampilan 6Cs (kolaborasi, karakter, kreativitas, berpikir kritis, kewarganegaraan, dan komunikasi) pada mata pelajaran Bahasa Arab. Melalui digital project-based learning berbasis kearifan lokal dengan pendekatan deep learning, mahasiswa mampu berinteraksi secara aktif dan lebih menikmati pembelajaran dalam mengembangkan keterampilan soft skills dan literasi digital secara holistik, menjadikannya model pembelajaran yang relevan di era digital.